FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KECEMASAN IBU BERSALIN KALA 1 FASE LATEN DI RUANG BERSALIN RUMAH SAKIT UMUM DAERAH KAYUAGUNG TAHUN 2022 - Titin Widia Sari; Fika Minata Wathan; Titin Dewi Sartika Silaban; Syarifah Ismed (LPPM STIKes Mitra Adiguna, 2023)
The psychological problem felt by the mother during childbirth is anxiety. Feelings of anxiety the birth process will result in complications in the delivery process. This study aims to determine the factors that influence the level of maternal anxiety during the first stage of the latent phase in the maternity ward of the Kayuagung Regional General Hospital in 2022. The research design used an analytical survey method through a cross sectional. The population in this study were all mothers who gave birth during the latent phase 1 in the Maternity Room of the Kayuagung Regional General Hospital. Sampling was an accidental sampling technique so that the number of samples was 34 respondents. Data was collected by means of a questionnaire. The data were analyzed by using the Chi-square test formula. Univariate analysis found that mothers experienced severe anxiety 13 respondents (38.2%), 15 respondents mild anxiety (44.1%) and mild anxiety 6 respondents (17.6%). Age at high risk 19 respondents (55.9%), low education 21 respondents (61.8%), high risk parity 18 respondents (52.9%) and family support supported 20 respondents (58.8%). The results showed that there was a relationship between age, education, parity and family support with the level of maternal anxiety in the first stage of the latent phase (p value <0.005). The conclusion is that there is a relationship between age, education, parity and family support with the level of anxiety of mothers giving birth in the delivery room of the Kayuagung General Hospital. Suggestions are expected that maternity mothers can be positive in dealing with childbirth and increase their knowledge so that they are more prepared to face childbirth.